MULTIDISCIPLINARY SCIENCE IN THE QURAN PERSPECTIVE (Tafsir Ilmi in Surah Al-Kahf Verses 60-82) - Al Azhari, Faisal Amri (Proceeding International Seminar of Islamic Studies, 2024)
This study of the interpretation of Surah al-Kahf verses 60-82 is to analyze various branches of knowledge in the Koran as a form of inspiration regarding multidisciplinary science. This group of verses describes the story of the scientific pursuit of the Prophet Musa as with one of Allah's servants who was given knowledge (in many interpretations his name is Khaidir as). This tafsir study focuses on Tafsir Ilmi, namely analyzing scientific signals from the perspective of modern science contained in the munasabah of this verse using a content analysis approach. Content analysis is linked to the latest scientific findings. So the conclusion obtained is that the scientific interpretation of these verses shows that these verses have already surpassed current contemporary scientific findings and are full of signs of multidisciplinary science. In fact, not only scientific content about futuristic science is found in these verses, but also many methods, approaches are found in the process of learning and conducting scientific research, but also character education, student etiquette towards teachers is also highly emphasized in the munasabah of this verse.